SAE Technical Paper Series 2014
DOI: 10.4271/2014-01-1195
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Turbulent Jet Characteristics on Engine Performance Using a Pre-Chamber Combustor

Abstract: Increasingly stringent US fuel economy regulation has emphasized the need for automotive engines to achieve greater levels of efficiency. Lean operation in spark ignition engines has demonstrated the ability to increase thermal efficiency, but this is typically accompanied by increased nitrogen oxides (NO x) emissions. Ultra-lean operation (λ > 2), however, has demonstrated increased thermal efficiency and the potential for significant reductions in NO x. Turbulent Jet Ignition (TJI) enables ultralean operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 20 publications
1
43
1
Order By: Relevance
“…Toulson [18] and Attard [19] compared the combustion process of PCC and SI under the same optical engine and found that the PCC ignition presents much faster and more stable combustion at λ=1.8 compared to the SI mode at λ=1.4. Bunce et al [20] applied high-speed OH* and CH* chemiluminescence imaging to evaluate the turbulent jet characteristics of a PCC engine. By comparing simultaneously acquired flame jet image and PC/MC pressure, they found that the first visible flame jets appeared around the peak of the PC pressure for different PC nozzle orifices diameter designs.…”
Section: Introductionmentioning
confidence: 99%
“…Toulson [18] and Attard [19] compared the combustion process of PCC and SI under the same optical engine and found that the PCC ignition presents much faster and more stable combustion at λ=1.8 compared to the SI mode at λ=1.4. Bunce et al [20] applied high-speed OH* and CH* chemiluminescence imaging to evaluate the turbulent jet characteristics of a PCC engine. By comparing simultaneously acquired flame jet image and PC/MC pressure, they found that the first visible flame jets appeared around the peak of the PC pressure for different PC nozzle orifices diameter designs.…”
Section: Introductionmentioning
confidence: 99%
“…Prechamber combustion can be referred to as a "prechamber combustor" [7], "prechamber ignition" [3], "torch ignition" [8][9][10], "jet ignition" [11][12][13][14][15][16], "two-stage combustion" [17][18][19], and "scavenged prechamber" [2,20]. Results from these studies validate the advantages of the fuel-added prechamber for SI engines and confirm the lean-burning and fuel-saving efficiencies of prechambers with an additional fuel delivery nozzle.…”
Section: Introductionmentioning
confidence: 65%
“…The engine speed was chosen as follows. Considering the simulation and experimental results of jet-ignition systems in [18,19], the main-combustion chamber burn duration of our jet ignition system was estimated to be around 20 crank degrees with λ = 1.75. From the RCM experimental data shown in Fig.…”
Section: Simulation Results and Experimental Valida-tionmentioning
confidence: 99%